T cell subsets differently regulate osteogenic differentiation of human mesenchymal stromal cells in vitro. (7th May 2013) - Grassi, Francesco; Cattini, Luca; Gambari, Laura; Manferdini, Cristina; Piacentini, Anna; Gabusi, Elena; Facchini, Andrea; Lisignoli, Gina
Abstract: T lymphocytes play a key role in the regulation of bone homeostasis and bone healing. The inflammatory response at the site of bone injury is essential to the initiation of the bone repair program; however, an uncontrolled exposure to inflammatory environment has a negative effect on tissue regeneration – indeed, activated T cells were shown to inhibit osteogenic differentiation on human mesenchymal stromal cells (MSCs). Whether resting T cells can induce osteogenic differentiation of MSCs and what role specific T cells subset play in this process is still elusive. In this study, we sought to analyse the osteogenic gene expression profile of whole T cells, CD4 and CD8 T cells isolated from healthy donors and investigated whether secreted factors from each group modulate osteogenic differentiation of human MSCs. Gene expression profiling identified a pool of 51 genes involved at various stages in bone growth which are expressed above detectable levels in CD4 and CD8 T cells. Most genes of this pool were expressed at higher levels in the CD4 subset. In vitro mineralization assays revealed that conditioned medium from CD4 T cells, but not from CD8 cells, significantly increased mineralization in osteogenic cultures of human MSCs; furthermore, mRNA expression of Runt‐related transcription factor 2 ( RUNX‐2 ), osteocalcin ( OC ), bone sialoprotein ( BSP ) and alkaline phosphatase ( ALP ) in MSCs was significantly upregulated in the presence of CD4‐conditioned medium but not with that obtained from CD8. The results show a differential role for CD4 and CD8 T cells in supporting bone formation and identify an osteogenic gene signature of each subset. Copyright © 2013 John Wiley & Sons, Ltd.